Preparation of copolymer of acrylamide and acrylic acid and its application for slow release sodium nitrate fertilizer - Mohammed A. Mutar; Rafid K. Kmal (Al-Qadisiyah Journal of Pure Science, 2017)
In this search The hydrogels were prepared by free-radical crosslinkig copolymerization of the monomer acrylamide (AAm) with acrylic acid (AA) as a crosslinker in aqueous solutions in the presence of potassium persulfate (KPS) as initiator and N,N,N',N'-tetramethylethylene-diamine (TEMED) as accelerator, polyacrylamide hydrogels structures were prepared by using acrylic acid (AA) (0.5, 1, 1.5, 2, 2.5) gm in the presence N,N'-methylene-bisacrylamide (MBA) as crosslinking agents at temperature 60 0c for 2 hours.The swelling ratio (Rs) was measured for all the hydrogel structures in aqueous solution as function of time at room temperature. Sodium nitrate was loaded into polymeric matrix during in situ polymerization. The concentration of sodium nitrate released was measured on flame photometer every 1 hr. The fertilizer release studies from the sodium nitrate loaded hydrogel was studied in aqueous solution as function of time at room temperature. The results showed that the samples involving the highest release of sodium nitrate were arranged as follows:PAAm-AA2.5gm > PAAm-AA2gm > PAAm-AA1.5gm > PAAm- AA1gm > PAAm-AA0.5gm